Interactional coping solutions: The case of a French legal firm - Feng, Min; Bourazzouq, Driss (Management international / International Management / Gestiòn Internacional, 2023)
This study analyzes qualitatively nine interactional coping solutions (ICS) in the post-adoption stage of information technology implementation at a French legal firm to understand the impact of these solutions on managing technostress. We captured the impact of interactional coping solutions (ICS) and noticed certain limitations within the firm that can impact the performance of interactional coping solutions (ICS) in managing technostress. These limitations include a lack of creative interaction between colleagues at the group level and of organizational commitment to the digitalization process.